2x+10+4(-x)=(-x)+(-20)

Simple and best practice solution for 2x+10+4(-x)=(-x)+(-20) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+10+4(-x)=(-x)+(-20) equation:


Simplifying
2x + 10 + 4(-1x) = (-1x) + (-20)

Remove parenthesis around (-1x)
2x + 10 + 4 * -1x = (-1x) + (-20)

Multiply 4 * -1
2x + 10 + -4x = (-1x) + (-20)

Reorder the terms:
10 + 2x + -4x = (-1x) + (-20)

Combine like terms: 2x + -4x = -2x
10 + -2x = (-1x) + (-20)
10 + -2x = (-1x) + -20

Reorder the terms:
10 + -2x = -20 + (-1x)

Solving
10 + -2x = -20 + (-1x)

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '(x)' to each side of the equation.
10 + -2x + (x) = -20 + (-1x) + (x)
10 + -2x + x = -20 + (-1x) + (x)

Combine like terms: -2x + x = -1x
10 + -1x = -20 + (-1x) + (x)
10 + -1x = -20 + (-1x) + x

Combine like terms: (-1x) + x = 0
10 + -1x = -20 + 0
10 + -1x = -20

Add '-10' to each side of the equation.
10 + -10 + -1x = -20 + -10

Combine like terms: 10 + -10 = 0
0 + -1x = -20 + -10
-1x = -20 + -10

Combine like terms: -20 + -10 = -30
-1x = -30

Divide each side by '-1'.
x = 30

Simplifying
x = 30

See similar equations:

| 10d+5=7d+32 | | 2/5x+3=9 | | (1.49+0.59+0.49)=30.84+0.30 | | (7x-8)(3x+9)= | | fx=-1x+x^3 | | 4/5=c/7 | | 3-x-9+15x= | | 3x+(-2x)+x=3x+18 | | 3t+8=5t+8-2t | | 3(x-4)=-1.2 | | 100x-29=42671 | | 1/4x-1/8x=3-1/16x | | 60x=100 | | 7(a+2)=34.3 | | x*3=18 | | 0.25y-3.5=0.15y+1-0.8y | | 100x-29=100(426.71) | | -2/3x+2=6 | | 3(-2x+1)-4(-x)=-x+19 | | 3(-2x+1)-4(-x)=x+19 | | 3t+2(t+1)+7t+6=-16 | | 3x+6=3x-12 | | 7m-25=-32+6m | | z-42=-41 | | 20=5c-3 | | 2(x-3)=3x+3 | | x-0.6=9.36 | | 7e-9=19.7 | | ax=5a | | n^3-n=7n^2-5 | | n^3-n=7n^2-5 | | 3x=b/a |

Equations solver categories